2020
DOI: 10.1117/1.nph.7.2.025002
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral hemodynamic monitoring of Parkinson’s disease patients with orthostatic intolerance during head-up tilt test

Abstract: Significance: Monitoring of cerebral perfusion rather than blood pressure changes during a head-up tilt test (HUTT) is proposed to understand the pathophysiological effect of orthostatic intolerance (OI), including orthostatic hypotension (OH), in Parkinson's disease (PD) patients. Aim: We aim to characterize and distinguish the cerebral perfusion response to a HUTT for healthy controls (HCs) and PD patients with OI symptoms. Approach: Thirty-nine PD patients with OI symptoms [10 PD patients with OH (PD-OH) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…The fNIRS response to the HUT was divided into five phases: baseline, dynamic tilt-up phase, static tilt phase, dynamic tilt-down phase, and post-tilt phase. The HUT protocol was performed in a similar method with reference to previous studies (Sundkvist and Lilja, 1983 ; Jahan et al, 1996 ; Kim et al, 2020b ). After a 20-min rest in the supine position, the baseline BP and HR were recorded (Task A).…”
Section: Methodsmentioning
confidence: 99%
“…The fNIRS response to the HUT was divided into five phases: baseline, dynamic tilt-up phase, static tilt phase, dynamic tilt-down phase, and post-tilt phase. The HUT protocol was performed in a similar method with reference to previous studies (Sundkvist and Lilja, 1983 ; Jahan et al, 1996 ; Kim et al, 2020b ). After a 20-min rest in the supine position, the baseline BP and HR were recorded (Task A).…”
Section: Methodsmentioning
confidence: 99%
“…[15][16][17] In our recent DOT study, we found that the rate of oxyhemoglobin (HbO) changes from the dynamic to the static tilt phase may be a sensitive marker for differentiating healthy controls (HCs) from PD patients with OH (PD-OH). 18 Our previous study also suggested that DOT measurements provide information on cerebral reoxygenation that cannot be gleaned from conventional BP monitoring during HUTT, particularly in patients with PD who have normal HUTT results (PD-NOR). 18 The regional analysis of the brain in PD-OH patients showed that specific cerebral structures are involved in autonomic control.…”
Section: Introductionmentioning
confidence: 99%
“…18 Our previous study also suggested that DOT measurements provide information on cerebral reoxygenation that cannot be gleaned from conventional BP monitoring during HUTT, particularly in patients with PD who have normal HUTT results (PD-NOR). 18 The regional analysis of the brain in PD-OH patients showed that specific cerebral structures are involved in autonomic control. Pathological studies have shown that neurodegenerative processes associated with alpha-synuclein pathology along the central structures are responsible for autonomic control, which may have implications for the pathophysiological mechanism underlying OH in patients with PD.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations